Peran Kemudahan Penggunaan dan Kepercayaan dalam Meningkatkan Kepuasan Pengguna Newsakpole - Diah Pita Sari; Andini Tiara Diva; Fani Kusuma Styaningrum; Akin Witri Gaoma; Nabila Olga Fawnia; Joko Tri Nugraha (PANDITA: Interdisciplinary Journal of Public Affairs, 2025)
This study aims to analyze the influence of ease of use and trust on the level of user satisfaction in utilizing the New Sakpole application of the Central Java Regional Police as a digital service for Motor Vehicle Tax (PKB) payment and annual STNK validation. The research employs a quantitative approach using a survey technique, in which data were collected through questionnaires distributed to active users of the application. Respondents were selected using purposive sampling with the criterion of having used the application at least once within the past year. The data were analyzed using multiple linear regression with the assistance of SmartPLS software. The results indicate that the ease of use variable has a positive and significant effect on user satisfaction. Similarly, the trust variable also shows a positive and significant influence on user satisfaction with the application. Simultaneously, both variables contribute strongly to determining the level of public satisfaction with the New Sakpole service. These findings emphasize that improving the quality of digital services particularly regarding ease of use and trust in process and data security should be a primary focus in the development of technology-based public service systems to enhance effectiveness, efficiency, and public loyalty toward government services.